2006
DOI: 10.1007/s10722-005-7110-8
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Diploid D-Genome Aegilops Tauschii Coss. in Iran Measured Using Microsatellites

Abstract: Microsatellite markers were used to analyse the biodiversity of 57 accessions of different subspecies and varieties of wild Aegilops tauschii (2n = 2x = 14; D genome) collected across the major areas where it grows in Iran. Levels of diversity were high, with numbers of alleles averaging 7.3 (ranging up to 12) and polymorphism information contents averaging 0.6591. One accession was notably more similar to two of the D genome in hexaploid wheats (Triticum aestivum) used as outgroups. Within the Ae. tauschii ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 29 publications
2
38
1
Order By: Relevance
“…squarrosa L. subspecies strangulata Eig) based on spikelet morphology, whereas the typical forms of subspecies tauschii and strangulata are connected by a continuous range of intermediate forms (Dudnikov 1998). Some recent reports have also shown difficulty in distinguishing the two subspecies based on molecular markers and suggested a high level of gene flow between them (Dvorak et al 1998, Dudnikov and Kawahara 2006, Saeidi et al 2006. Two characteristics that distinguish the subspecies have been described: one is glume width to rachis segment width ratio, another is allozyme variation at the Acph1 locus (Dudnikov 2000).…”
Section: Introductionmentioning
confidence: 99%
“…squarrosa L. subspecies strangulata Eig) based on spikelet morphology, whereas the typical forms of subspecies tauschii and strangulata are connected by a continuous range of intermediate forms (Dudnikov 1998). Some recent reports have also shown difficulty in distinguishing the two subspecies based on molecular markers and suggested a high level of gene flow between them (Dvorak et al 1998, Dudnikov and Kawahara 2006, Saeidi et al 2006. Two characteristics that distinguish the subspecies have been described: one is glume width to rachis segment width ratio, another is allozyme variation at the Acph1 locus (Dudnikov 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that IRAPs can reveal levels of diversity that could not be revealed by using powerful co-dominant markers such as SSRs (see Saeidi et al 2006Saeidi et al , 2008. The results of this study showed that they are reliable molecular markers for study genetic diversity of species such as H. murinum, in particular, for which limited specific SSR markers are available and show low SSR transferability from congener species.…”
Section: Discussionmentioning
confidence: 76%
“…This region is the center of Ae. tauschii distribution (Van Slageren 1994) where the species shows phenotypic, genetic, and ecological diversity (Kihara et al 1965;Dvorak et al 1998;Dudnikov and Kawahara 2006;Saeidi et al 2006). Kihara et al (1965) observed that in Ghoznavi, a village near Kosh-Yeylagh, Ae.…”
Section: Study Areamentioning
confidence: 99%